KEMITRAAN INDONESIA DAN GLOBAL FUND DALAM MENGATASI PENYAKIT TBC DI INDONESIA - Farahdiba Rahma Bachtiar (Review of International Relations, 2022)
This research focuses on the partnership between Global Fund and Indonesia. For this reason, this paper answers the question of what are the forms and models of partnerships carried out between Global Fund and Indonesia in overcoming the infectious disease Tuberculosis. This study uses the conceptual framework of global health security and human security to see the partnership that exists between GF and Indonesia which has been going on since 2003. This research focuses on the existence of three important aspects in the implementation of the global health security partnership which include: normative aspects, institutional aspects and practical aspects of how the implementation of the global security health policy can be completed. This research finds that these three aspects are fulfilled and are the key to the success of the partnership which continue between the GF, the central government, local government and community institutions through programs funded in a three-year cycle and carried out in a long term (round). For this reason, these three aspects must continue to be encouraged and evaluated in order to create wider impact.